Transcranial direct current stimulation for gait recovery following stroke: A systematic review of current literature and beyond - Corominas-Teruel, Xavier; Mozo, Rosa María San Segundo; Simó, Montserrat Fibla; Colomina Fosch, Maria Teresa; Valero-Cabré, Antoni (Frontiers in Neurology, 2022)
Background Over the last decade, transcranial direct current stimulation (tDCS) has set promise contributing to post-stroke gait rehabilitation. Even so, results are still inconsistent due to low sample size, heterogeneity of samples, and tDCS design differences preventing comparability. Nonetheless, updated knowledge in post-stroke neurophysiology and stimulation technologies opens up opportunities to massively improve treatments. Objective The current systematic review aims to summarize the current state-of-the-art on the effects of tDCS applied to stroke subjects for gait rehabilitation, discuss tDCS strategies factoring individual subject profiles, and highlight new promising strategies. Methods MEDLINE, SCOPUS, CENTRAL, and CINAHL were searched for stroke randomized clinical trials using tDCS for the recovery of gait before 7 February 2022. In order to provide statistical support to the current review, we analyzed the achieved effect sizes and performed statistical comparisons. Results A total of 24 records were finally included in our review, totaling n = 651 subjects. Detailed analyses revealed n = 4 (17%) studies with large effect sizes (≥0.8), n = 6 (25%) studies with medium ones (≥0.5), and n = 6 (25%) studies yielding low effects sizes (≤ 0.2). Statistically significant negative correlations (rho = −0.65, p = 0.04) and differences (p = 0.03) argued in favor of tDCS interventions in the sub-acute phase. Finally, significant differences (p = 0.03) were argued in favor of a bifocal stimulation montage (anodal M1 ipsilesional and cathodal M1 contralesional) with respect to anodal ipsilesional M1. Conclusion Our systematic review highlights the potential of tDCS to contribute to gait recovery following stroke, although also the urgent need to improve current stimulation strategies and subject-customized interventions considering stroke severity, type or time-course, and the use of network-based multifocal stimulation approaches guided by computational biophysical modeling. Systematic review registration PROSPERO: CRD42021256347.